Software engineering for embedded systems : methods, practical techniques, and applications - Oshana, Robert; Kraeling, Mark (Expert guide, 2013)
And conclusions -- Introduction to debugging tools -- GDB debugging -- Configure the GDB debugger -- Starting GDB -- Compiling the application -- Debugging the application -- Examining data -- Using breakpoints -- Stepping -- Changing the program -- Analyzing core dumps -- Debug agent design -- Use cases -- Debug agent overview -- Starting the application -- Context switch -- Position-independent executables -- Debug event from the application -- Multicore -- Starting the debug agent -- Debugging using JTAG -- Benefits of using JTAG -- Board bring-up using JTAG -- Comparison with the debug agent -- GDB and JTAG -- Debugging tools using Eclipse and GDB -- Linux application debug with GDB -- Linux kernel debug with KGDB -- Instrumented code -- Practical example -- Analysis tools -- Strace -- Mtrace -- Vaigrind -- Hardware capabilities -- Hardware breakpoints -- Hardware watchpoints -- Debugging tips and tricks -- Part 1: Analysis and high-level design -- Analysis.